KAJIAN KEPEMIMPINAN BUDDHA - Dewi Astuti; Kabri * (Dharmasmrti: Jurnal Ilmu Agama dan Kebudayaan, 2024)
Leadership is an important aspect in human life. The concept of leadership has become the main subject of discussion in various scientific disciplines and society. This study seeks to examine leadership in Buddhism. This research uses a qualitative approach with a focus on library research. The Buddha's leadership has criteria laid down in the Dasa Raja Dhamma for a king or leader to carry out. The study of Buddhist leadership provides valuable insight into how Buddhist values of ethics, compassion and wisdom can form the basis of ethical and ethical leadership.